Myeloid HMG-CoA (3-Hydroxy-3-Methylglutaryl-Coenzyme A) Reductase Determines Atherosclerosis by Modulating Migration of Macrophages. Issue 11 (November 2018) - Sakai, Kent; Nagashima, Shuichi; Wakabayashi, Tetsuji; Tumenbayar, Bayasgalan; Hayakawa, Hiroko; Hayakawa, Morisada; Karasawa, Tadayoshi; Ohashi, Ken; Yamazaki, Hisataka; Takei, Akihito; Takei, Shoko; Yamamuro, Daisuke; et al.
Abstract : Objective—: Inhibition of HMGCR (3-hydroxy-3-methylglutaryl-coenzyme A reductase) is atheroprotective primarily by decreasing plasma LDL (low-density lipoprotein)-cholesterol. However, it is unknown whether inhibition of HMGCR in myeloid cells contributes to this atheroprotection. We sought to determine the role of myeloid HMGCR in the development of atherosclerosis. Approach and Results—: We generated mice with genetically reduced Hmgcr in myeloid cells ( Hmgcr m− /m − ) using LysM (Cre) and compared various functions of their macrophages to those of Hmgcr fl/fl control mice. We further compared the extent of atherosclerosis in Hmgcr m −/ m − and Hmgcr fl/fl mice in the absence of Ldlr (LDL receptor). Hmgcr m −/ m − macrophages and granulocytes had significantly lower Hmgcr mRNA expression and cholesterol biosynthesis than Hmgcr fl/fl cells. In vitro, Hmgcr m −/ m − monocytes/macrophages had reduced ability to migrate, proliferate, and survive compared with Hmgcr fl/fl monocytes/macrophages. However, there was no difference in ability to adhere, phagocytose, store lipids, or polarize to M1 macrophages between the 2 types of macrophages. The amounts of plasma membrane–associated small GTPase proteins, such as RhoA (RAS homolog family member A), were increased in Hmgcr m −/ m − macrophages. In the setting of Ldlr deficiency, Hmgcr m −/ m − mice developed significantly smaller atherosclerotic lesions than Hmgcr fl/fl mice. However, there were no differences between the 2 types of mice either in plasma lipoprotein profiles or in the numbers of proliferating or apoptotic cells in the lesions in vivo. The in vivo migration of Hmgcr m −/ m − macrophages to the lesions was reduced compared with Hmgcr fl/fl macrophages. Conclusions—: Genetic reduction of HMGCR in myeloid cells may exert atheroprotective effects primarily by decreasing the migratory activity of monocytes/macrophages to the lesions. Abstract : Supplemental Digital Content is available in the text.